Los estudios de opinión instrumento de validación de la realidad social (2005)
ABSTRACT: In the case of opinion surveys, we have seen a lot of practice and very little theoretical reflection. Their existence is approved by all but, in parallel, there has been very little discussion of conceptual, so such epistemological that his status is precarious and simply relying on empirical studies that offers guidance microsociológica, so that, Indeed, these studies are located in the area of empirical sociology.